Commonwealth-State financial relations in Australia - Maxwell, James A. (London : Melbourne University Press, 1967)
This is the first examination of Australia's experiments in federal finance-experiments contributing to the theory and practice of federalism.
Includes bibliographical references and index.
osc 30/06/2017
Loans
Keywords: Finance